2018
DOI: 10.1016/j.critrevonc.2018.08.011
|View full text |Cite
|
Sign up to set email alerts
|

The Era of PARP inhibitors in ovarian cancer: “Class Action” or not? A systematic review and meta-analysis

Abstract: Introduction: Carboplatin is the milestone of epithelial ovarian cancer (EOC) treatment, thus response to platinum is the major prognostic factor. Among platinum-sensitive patients, 40% carry a germline or somatic BRCA1/2 mutation. In this scenario a new class of drugs, the PARP inhibitors (PARPis), produced a significant improvement in long-term disease control. In order to make an aggregate evaluation of the impact of these agents, we performed a systematic review and meta-analysis. Patients and Methods: Cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 53 publications
(50 reference statements)
1
24
0
Order By: Relevance
“…In ovarian cancer, these targeted inhibitors were the standard treatment for advanced serous ovarian cancer with BRCA mutation [35,36], and could also be used as alternative treatment for many patients other than BRCA germline mutation carriers [33,36]. At present, some scholars have analyzed the effect of PARPis on the treatment of ovarian cancer patients through meta-analysis [37,38]. However, more randomized controlled trials have been included in this study, including some of the latest clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…In ovarian cancer, these targeted inhibitors were the standard treatment for advanced serous ovarian cancer with BRCA mutation [35,36], and could also be used as alternative treatment for many patients other than BRCA germline mutation carriers [33,36]. At present, some scholars have analyzed the effect of PARPis on the treatment of ovarian cancer patients through meta-analysis [37,38]. However, more randomized controlled trials have been included in this study, including some of the latest clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Many adverse events of PARPi treatment are class effects, meaning that all the drugs of the PARPi family are associated with these specific adverse events. 41 However, it is important to recognize specific drug-to-drug differences, including non-class effect adverse events as well as different incidence of the class effect adverse events. A meta-analysis examining the differences in toxicity between olaparib, niraparib, and rucaparib showed that hematologic adverse events were significantly related to niraparib, abdominal pain to rucaparib, and diarrhea to olaparib.…”
Section: Management Of Adverse Eventsmentioning
confidence: 99%
“…A meta-analysis examining the differences in toxicity between olaparib, niraparib, and rucaparib showed that hematologic adverse events were significantly related to niraparib, abdominal pain to rucaparib, and diarrhea to olaparib. 41 It is important to note that there is currently a recommendation to dose-adjust niraparib according to platelet level and weight at baseline, which was not yet incorporated in the trials assessed in the meta-analysis. 19 42 Table 3 summarizes adverse events in PARPi maintenance treatment in ovarian cancer in front-line and recurrent settings.…”
Section: Management Of Adverse Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many AEs are class effects, such as cytopenia, but some are more dependent on the drug involved. A meta-analysis detected no significant differences in all grade hematologic AEs, more frequent in the initial months, however severe hematologic AEs were found to be more frequent with niraparib [ 47 ]. Niraparib is now recommended to be started at 200mg daily in patients with weight < 77 kg or with a low platelet count < 150 × 109 cells/L after a retrospective analysis of the NOVA trial [ 48 ].…”
Section: Dna Repairs Defect and Poly (Adenosine Disphosphate-ribosmentioning
confidence: 99%